Black Dwarf Honey Bee, Apis andreniformis Smith, 1858 (Insecta: Hymenoptera: Apidae) - Mary Nordgulen; Brynn Johnson; Cameron Jack (EDIS)
Contents: Introduction - Synonymy - Distribution - Description - Life Cycle and Biology – Economic Importance - Management - Selected References